Ensemble coding of face identity is present but weaker in congenital prosopagnosia. (March 2018) - Robson, Matthew K.; Palermo, Romina; Jeffery, Linda; Neumann, Markus F.
Abstract: Individuals with congenital prosopagnosia (CP) are impaired at identifying individual faces but do not appear to show impairments in extracting the average identity from a group of faces (known as ensemble coding ). However, possible deficits in ensemble coding in a previous study (CPs n = 4) may have been masked because CPs relied on pictorial (image) cues rather than identity cues. Here we asked whether a larger sample of CPs ( n = 11) would show intact ensemble coding of identity when availability of image cues was minimised. Participants viewed a "set" of four faces and then judged whether a subsequent individual test face, either an exemplar or a "set average", was in the preceding set. Ensemble coding occurred when matching (vs. mismatching) averages were mistakenly endorsed as set members. We assessed both image- and identity-based ensemble coding, by varying whether test faces were either the same or different images of the identities in the set. CPs showed significant ensemble coding in both tasks, indicating that their performance was independent of image cues. As a group, CPs' ensemble coding was weaker than controls in both tasks, consistent with evidence that perceptual processing of face identity is disrupted in CP. This effect was driven by CPs (n= 3) who, in addition to having impaired face memory, also performed particularly poorly on a measure of face perception (CFPT). Future research, using larger samples, should examine whether deficits in ensemble coding may be restricted to CPs who also have substantial face perception deficits. Highlights: Ensemble coding of identity is weaker in congenital prosopagnosia than in controls. This may be driven by prosopagnosics with significant face perception deficits. Ensemble coding of identity in congenital prosopagnosia is not image-dependent. Exemplar and ensemble coding identity processes are related.